2015
DOI: 10.1016/j.bbalip.2015.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Short-chain polyisoprenoids in the yeast Saccharomyces cerevisiae — New companions of the old guys

Abstract: Dolichols are, among others, obligatory cofactors of protein glycosylation in eukaryotic cells. It is well known that yeast cells accumulate a family of dolichols with Dol-15/16 dominating while upon certain physiological conditions a second family with Dol-21 dominating is noted. In this report we identified the presence of additional short-chain length polyprenols - all-trans Pren-7 in three yeast strains (SS328, BY4741 and L5366), Pren-7 was accompanied by traces of putative Pren-6 and -8. Moreover, in two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…An initial HPLC/UV analysis of polyprenols isolated from T. reesei revealed a complex mixture containing numerous additional compounds besides those found in mammalian or S. cerevisiae cells and eluting with retention times corresponding to Dol-18–Dol-20. This was confirmed by the finer liquid chromatography electrospray ionization-quadrupole-time of flight-mass spectrometry (LC-ESI-QTOF-MS, liquide chromatography electrospray ionization-quadrupole-time of flight-mass spectrometry) analysis again showing a much more complex mixture of compounds (Table 1, Figure S1) than that reported for S. cerevisiae (Dol-14 to Dol-18 with Dol-16 dominating) [5,6,7]. An LC-ESI-QTOF-MS analysis showed that the polyprenols from T. reesei comprise a complex mixture of compounds with 18, 19 or 20 isoprene units and an apparently different degree of saturation (Table 1, a full list is presented in Table S1).…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…An initial HPLC/UV analysis of polyprenols isolated from T. reesei revealed a complex mixture containing numerous additional compounds besides those found in mammalian or S. cerevisiae cells and eluting with retention times corresponding to Dol-18–Dol-20. This was confirmed by the finer liquid chromatography electrospray ionization-quadrupole-time of flight-mass spectrometry (LC-ESI-QTOF-MS, liquide chromatography electrospray ionization-quadrupole-time of flight-mass spectrometry) analysis again showing a much more complex mixture of compounds (Table 1, Figure S1) than that reported for S. cerevisiae (Dol-14 to Dol-18 with Dol-16 dominating) [5,6,7]. An LC-ESI-QTOF-MS analysis showed that the polyprenols from T. reesei comprise a complex mixture of compounds with 18, 19 or 20 isoprene units and an apparently different degree of saturation (Table 1, a full list is presented in Table S1).…”
Section: Resultssupporting
confidence: 58%
“…The only dolichols from filamentous fungi described so far were those isolated from A. niger [11] and A. fumigatus [10], and rather unexpectedly they were found to differ structurally from typical dolichols, as exemplified by those from animals or S. cerevisiae . In addition to these structural differences, they were also longer than the yeast ones, which are up to 22 isoprene units long [5,6,7]. A. niger contained a family of exo-methylenehexahydroprenols of between 18 and 24 isoprene residues, and A. fumigatus had dolichols with two or three hydrogenated isoprenoid residues located at the ω-end.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Tanaka presumed that the biosynthesis of natural rubber starts with an unidentified initiating species containing two trans-isoprene units and a peptide group [52], it is possible to assume that one intermediate in the biosynthetic pathway of rubber might be an epoxy compound of a rubber-like polyprenol. characterization of a C 55 polyprenol detected at the stationary phase of growth of some yeast strains indicated the presence of internal two trans-isoprene residues [41]. Pig liver also contains a family of shorter-chain polyprenols dominated by a C 55 -dolichol and a long chain (C 95-100 ) dolichol [42].…”
Section: Poly-cis Prenolmentioning
confidence: 99%
“…Yeast polyisoprenoid: Yeast cells were harvested by centrifugation of 100 mL of yeast culture at 3300× g (Allegra; Beckman, Indianapolis, IN, USA) for 10 min at room temperature, washed with water and hydrolyzed for 1 h at 95 °C in 10 mL of solution containing 25% KOH and 65% ethanol supplemented with internal standard Pren-28 (10 μg). Subsequently, lipids were extracted with hexane, purified on silica gel columns, dissolved in propan-2-ol and analyzed as described earlier [36].…”
Section: Methodsmentioning
confidence: 99%